التقدير الأولي لكلفة مشروعات الأبنية باستخدام الشبكات العصبونية - حمد, ابتسام; نجا, هاني; أفندي, رهف عمر (Latakia University Journal -Engineering Sciences Series, 2019)
يقوم التقدير الأولي لكلفة أعمال البناء بوظيفة مهمة في عملية اتخاذ القرار للمشاريع على الرغم من محدودية بيانات التصميم المتاحة في تلك المرحلة؛ لذلك هدفت هذه الدراسة إلى تطوير موديل نموذجي لتقدير كلفة مشاريع الأبنية في المرحلة الأولية للمشاريع باستخدام تقنية الشبكات العصبونية الصنعية، فتم جمع بيانات لـ38 بناء سكني في محافظة اللاذقية، وحددت مجموعة من البارامترات المهمة المؤثرة في كلفة الأبنية السكنية على الهيكل، وذلك من خلال توزيع استبيان على عدد من المهندسين الاستشاريين في هذا المجال، وتم تدريب الشبكة العصبونية، واختبارها من خلال مجموعة من التصاميم المعمارية المقترحة، وتم اعتماد معمارية الشبكة العصبونية المثلى ذات الخطأ الأصغري. تتألف طبقة الدخل للشبكة العصبونية المقترحة من إحد عشر متغيراً، وتتضمن طبقتين خفيتين كل طبقة تحتوي 14 عصبوناً، أما طبقة الخرج فتتألف من عصبون واحد يمثل كلفة المتر المربع للبناء على الهيكل. أشارت النتائج التي تم الحصول عليها من الشبكات العصبونية إلى نجاح هذه التقنية في التنبؤ بكلفة مشاريع الأبنية في المرحلة المبكرة من المشروع؛ وذلك اعتماداً على مجموعة من المعلومات دون حاجة إلى المزيد من التفاصيل المتعلقة بالتصميم، كذلك تم تطوير برنامج بسيط باستخدام لغة الـVB لتشغيل الشبكة العصبونية المدربة بسهولة. Early stage cost estimate plays a significant role in any initial construction project decisions, despite the project scope has not yet been finalized and still very limited information regarding the detailed design is available during these early stages. This study aimed at developing an efficient model to estimate the cost of building construction projects at conceptual stage of the project using artificial neural networks. Data of 38 building projects in Lattakia was collected. Several significant parameters identified for the structural skeleton cost of the project were determined by the use of questionnaire distributed among many experience engineers and constructors involved in this kind of projects, the network was trained and tested for different architectures in order to choose the network architecture that lead to the minimum error. The input layer of the artificial Neural Networks (ANN) model comprised eleven parameters. The developed ANN model had tow hidden layer with fourteen neuron. One neuron representing the meter square cost of structural buildings at conceptual stage of the project formed the output layer of the ANN model. The results obtained from the trained models indicated the neural networks reasonably succeeded in predicting the early stage cost estimation of buildings using basic information of the projects and without the need for more detailed design. Using VB programming language, simple program has been developed to run the trained network easily by the user.